Relationship between Islamic Social Finance and Sustainable Development Goals: A Conceptual Framework - Notolegowo, Hantoro Ksaid; Alamsyah, Indra Fajar; Saraswati, Nindya; Jalil, Bt Abdul; Bt Isahak Merican, Farah Merican (KnE Social Sciences, 2023)
The success of a country’s economic development can be assessed by the extent to which the Sustainable Development Goals (SDGs) are achieved. However, many developing countries face challenges in attaining the SDGs, often due to budget constraints. To overcome these obstacles, the presence of Islamic social finance, also known as ZISWAF (Zakat, Infaq, Sadaqat, and Waqf), is expected to play a significant role. Islamic social finance aims to address social and economic issues such as poverty and income inequality. This study aims to analyze the role of Islamic social finance (ISF) in the context of the SDGs. As Islamic social finance adheres to principles that align with the SDGs, it is essential to investigate whether ISF can support the achievement of the SDGs through its funding activities. The role of Islamic social finance in relation to the SDGs can be observed by examining the programs funded by ISF and assessing their alignment with the SDGs. The analytical approach employed in this study is descriptive and qualitative, aiming to explain the role of Islamic social finance in the SDGs. The analysis draws insights from relevant literature and data, and a conceptual framework is formulated to illustrate the relationship between Islamic social finance and the SDGs. The findings highlight the important role of Islamic social finance, including zakat, in contributing to the achievement of the SDGs. Through several case studies in various countries, Islamic social finance has demonstrated its potential to support the attainment of SDGs 1, 2, 3, 4, 8, 9, 11, and 12. These results emphasize the significant contribution of Islamic social finance in the success of SDGs programs, underscoring its potential as a tool for achieving the SDGs. Keywords: Islamic social finance, SDGs, relationship